The Effect of Low-intensity TRX Suspension Training with Blood Flow Restriction on Serum Levels of Angiogenesis Factors VEGF, HIF-1, and Body Composition in Active Female - Parisa Basiri; Kazem Khodaei; Javad Toloei-azar (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Resistance training with blood flow restriction increases the recruitment of fast-twitch fibers in hypoxia conditions. It also boosts the synthesis of muscle protein with anabolic hormone indices. Therefore, the purpose of the present study was to investigate the effect of low-intensity TRX suspension training with blood flow restriction on vascular endothelial growth factor (VEGF), hypoxia-inducible factor-1 (HIF-1), and body composition in active female students. Methods: The present semi-experimental study was conducted on 36 female physical education students. The samples were selected purposefully and then randomly divided into three groups, namely high-intensity TRX suspension training, low-intensity TRX suspension training with blood flow restriction, and control. The training groups performed three sessions of TRX exercises with and without blood flow restriction for eight weeks. Analysis of covariance (ANCOVA) and Bonferroni post hoc test were used to compare the results between groups. Results: The findings showed that eight-week low-intensity TRX training with blood flow restriction caused a significant increase in VEGF (P=0.001), HIF-1 (P=0.001), and total body muscle mass (P=0.008) compared to the control group. The high-intensity TRX training group also increased VEGF (P=0.018) and HIF-1 (P=0.002) compared to the control group. However, the low-intensity TRX training group with blood flow restriction led to a significant increase in HIF-1 concentration compared to the high-intensity TRX training group (P=0.031). TRX suspension training with and without blood flow restriction had no significant impact on body mass index, body fat percentage, and total body water (P<0.05). Conclusion: Overall, the results of this research showed that performing eight-week low-intensity TRX training with blood flow restriction improved the levels of VEGF, HIF-1, and muscle mass in active females. Therefore, these exercises can be a suitable training method to improve angiogenesis factors and body composition in females.